FAKTOR-FAKTOR YANG MEMPENGARUHI PELAKSANAAN COACHING TERHADAP PRESTASI PEKERJA DALAM ORGANISASI - Hisham@Dalha, Siti Noraqilah; Wan Muda, Wan Hanim Nadrah (Online Journal for TVET Practitioners, 2018)
Coaching is a one of the methods to guide employees in improving performance and assisting employees in identifying employee’s talent in an organization. Workers can highlight talent in the field of exploration through coaching. From previous studies, coaching was found to support development of employee’s performance. Nevertheless, some coaching programs are not well received and less effective in improving employee’s performance. As such, a study was conducted to identify and evaluate the factors of the effectiveness of coaching implementation on employee performance in organization. The quantitative method was applied to conduct this study and used descriptive and inferential study. Questionnaire were distributed to 138 staff of Politeknik Melaka, Melaka. Data collected were analyzed using Spearman Rho, One-way ANOVA and T-test. The result implied that there are three factors affected coaching on working performance consist of worker, coach and organization. Organization is the dominant factors which is affect the most of the coaching. This study expressed that coaching implementation provides the positive impact to the employees after the program. They thought that coaching program will help them to improve their working quality and recognizes the talent and skills in themselves.